Penguatan Kelembagaan Penanganan Pengungsi pada Agenda 2030 Sustainable Development Goals - Azaria, Davilla Prawidya (Esensi Hukum, 2022)
The protracted crisis of refugees as a marginal group is often neglected to fulfill their fundamental rights and well being in the sustainable development agenda. This paper aims to analyze well being indicators of refugees in the sustainable development agenda. The method used is normative research through literature study with a conceptual and analytical approach. The term of refugee are not written explicitly in the sustainable development agenda indicators as of they should be aligned with the general goals of the sustainable agenda, as well as institutional strengthening through policy reform, long-term financing, and requiring active cooperation from various actors in managing and fulfilling refugees fundamental rights, especially for hosting countries and humanitarian institutions at the global and national level.